Extrusion Conditions and Amylose Content Affect Physicochemical Properties of Extrudates Obtained from Brown Rice Grains. (23rd May 2013) - González, Rolando José; Pastor Cavada, Elena; Vioque Peña, Javier; Torres, Roberto Luis; De Greef, Dardo Mario; Drago, Silvina Rosa
Abstract : The utilization of whole grains in food formulations is nowadays recommended. Extrusion cooking allows obtaining precooked cereal products and a wide range of ready-to-eat foods. Two rice varieties having different amylose content (Fortuna 16% and Paso 144, 27%) were extruded using a Brabender single screw extruder. Factorial experimental design was used to study the effects of extrusion temperature (160, 175, and 190°C) and grits moisture content (14%, 16.5%, and 19%) on extrudate properties. Specific mechanical energy consumption (SMEC), radial expansion (E ), specific volume (SV), water absorption (WA), and solubility (S ) were determined on each extrudate sample. In general, Fortuna variety showed higher values of SMEC andS (703–409 versus 637–407 J/g; 33.0–21.0 versus 20.1–11.0%, resp.) than those of Paso 144; on the contrary SV (8.64–3.47 versus 8.27–4.53 mL/g) and WA tended to be lower (7.7–5.1 versus 8.4–6.6 mL/g). Both varieties showed similar values of expansion rate (3.60–2.18). Physical characteristics depended on extrusion conditions and rice variety used. The degree of cooking reached by Paso rice samples was lower than that obtained for Fortuna. It is suggested that the presence of germ and bran interfered with the cooking process, decreasing friction level and broadening residence time distribution.